Regional Tax Management Optimization Model to Realize Regional Financial Independence in Pekanbaru City, Riau Province - Kurniawan, Alek; Akbar, Bahrullah; Sinurat, Marja; Meltarini (Global Writing Academica Researching and Publishing, 2024)
The financial independence of the Pekanbaru City area is based on the amount of the original regional income, especially the local tax revenue. The purpose of the research is to analyze the determination of regional tax targets with real potential, analyze the process of optimizing regional taxes for regional financial independence, and find a regional tax optimization model for regional financial independence in Pekanbaru City, Riau Province. The research used qualitative research with 12 units of analysis with 20 informants who were determined by purposive sampling. Secondary data collection using literature studies and primary data using interview techniques based on optimizing local tax management by observation. Data analysis uses descriptive analysis developed by triangulation of observers. The results of the study concluded that the determination of regional tax targets was carried out by expanding the revenue base by improving the database and assessment of local taxes determined based on the collection process and improving the supervision process, the application of sanctions to improve administrative efficiency and cooperation between agencies in Pekanbaru City, Riau Province, the process of optimizing local taxes is carried out by intensification and extension of tax subjects and objects to increase regional financial independence, and the regional tax optimization model is: Model Four Pillars of Optimization of Regional Tax Management in the context of financial independence based on intensification and extension, institutional and information system. It is recommended to increase the efficiency of tax administration and reduce collection costs through improving administrative procedures and increasing the efficiency of collecting each type of local tax as well as carrying out better tax planning by improving the coordination of related agencies within the regional government of Pekanbaru City, Riau Province.